(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Information Technology (IT) industry undergoes many changes in recent times. To sustain in the changing environment, it is necessary to identify the changes and manage the changes. This study was undertaken to explore change management in IT services organisations. The results indicate that before evaluating the change efforts in the organisation it is important to consider the timely decision, self-interest, recognition of employees, and altering the organisational structure.